Asylum Seekers in Domestic and International Law: Emphasis on the Right to Family Reunification: Law on Asylum, Law on Foreigners, and Article 8 ECHR and ECtHR Jurisprudence - Slijepčević, Ljuba (Zbornik Instituta za kriminološka i sociološka istraživanja, 2018)
One of the basic elements of state sovereignty is the right of states to regulate the entry, exit, and residence of aliens in its teritory. The right to asylum is a category of international law. The right to asylum is provided in Article 14, paragraph 1 of the Universal Declaration of Human Rights of 1948: "Everyone has the right to seek and to enjoy in other countries asylum from persecution". Although the earlier Republic of Serbia had the Asylum Law published in the "Official Gazette of RS", no. 109/2007, which entered into force in April 2008, at a session of the National Assembly on 22 March 2018, adopted a new Law on asylum and temporary protection as well as the Law on Foreigners. The adoption of these new laws in Serbia harmonize its legislation with the EU acquis and strives to make the asylum procedure more efficient and to better define the rights and obligations of aliens in the Republic of Serbia. And one and other law is regulated by the law on family reunification that protects the provisions of Article 8 of the European Convention on Human Rights, and the European Court of Human Rights in this regard has a rich case law, provided that it first qualified the deportation of an alien as a violation of the right to a family life in 1991.